THE OBSTRUCTION OF THE ADMINISTRATION OF JUSTICE AND PRELIMINARY INVESTIGATION: PROBLEMS OF THE OBJECT AND THE OBJECTIVE SIDE - A. V. Boyarskaya (Правоприменение, 2018)
The subject. The article is devoted to the investigation of the main direct object and the circle of victims are subjected of harm by criminal acts stipulated by pts. 1, 2 of art. 294 of the Criminal Code of the Russian Federation.The purpose of the paper is to identify does the art. 294 of Criminal Code of the Russian Federation meets the other provisions of criminal procedure legislation.The methodology of research includes methods of complex analysis, synthesis, as well as formal-logical, comparative legal and formal-legal methods.Results and scope of application. The content of art. 294 of the Criminal Code of the Russian Federation does not comply with the provisions of the criminal procedure law. The discrep-ancy lies in terms of the range of participants in criminal proceedings and the functions performed by them, as well as the actual content and correlation of such stages of criminal proceedings as the initiation of criminal proceedings and preliminary investigation. In addi-tion, the current state of art. 294 of the Criminal Code of the Russian Federation does not take into account the ever-widening differentiation of criminal proceedings.The circle of victims listed in pt. 2 of art. 294 of the Criminal Code of the Russian Federation should be supplemented by such participants in the criminal process as a criminal investi-gator, the head of the investigative body, the head of the inquiry department, the head of the body of inquiry. At the same time, the author supports the position that the criminal-legal protection of the said persons should cover not only their activities at the stage of preliminary investigation, but also of the entire pre-trial proceedings as a whole.The circle of criminal acts provided for in art. 294 of the Criminal Code of the Russian Fed-eration, should also be specified with an indication of encroachment in the form of kidnapping, destruction or damage to such a crime as materials of criminal, civil and other cases, as well as material evidence.Conclusions. The content of art. 294 of the Criminal Code of the Russian Federation does not comply with the provisions of the criminal procedure law. The author formulates the conclusion that the circle of victims listed in pt. 2 of art. 294 of the Criminal Code should be broadened and joins the position that the criminal-legal protection of these persons should cover not only their activities at the stage of preliminary investigation, but also of the entire pre-trial proceedings as a whole.